Academic achievement as status competition: Intergenerational transmission of positional advantage among Taiwanese and American students. (April 2016) - Tam, Tony
This article compares the intergenerational transmission of relative/positional advantage for the academic achievement of secondary school students in Taiwan and the USA. Although any monotonic transformation of rank order is a valid measure of positional status, we use 'the average number of competitors excluded' as the index of positional status (PSI) because it is a ratio-scale metric easy to interpret and universally comparable—even among different variables and achievement test scores based on completely different tests. A PSI analysis of two large-scale national surveys of secondary school students (TEPS and NELS) shows that parental education plays a much stronger role than family income in both societies. Most important, parental education and income effects on the PSI are statistically indistinguishable between the two societies, despite very substantial differences in the institution of secondary education, including the screening and allocation of secondary students for higher education. This resemblance is especially striking given the large cross-national variation in the same PSI-based measures of intergenerational transmission of positional advantage among Organisation for Economic Co-operation and Development (OECD) countries.